COMPARISON OF THE EFFECT OF E-LEARNING ON LEARNING OUTCOMES STUDENTS DEPARTMENT OF ENGINEERING AND MANAGEMENT MAJORING IN MERCU BUANA UNIVERSITY - Viciwati, Viciwati (Dinasti International Journal of Management Science, 2021)
In today's digital era, it affects all aspects, including in the world of education. Some students do not only study on campus but they also learn by e-learning. However, since the corona pandemic, all the world of education has been carried out using e-learning. Seeing this phenomenon, the authors need to examine the comparison of Learning Outcomes between engineering and non-technical students because engineering students certainly need practical learning while non-technical children in this case such as management can learn E learning. The test used is the Independent Sample T test because the data is normally distributed. The results showed that there was no difference in learning outcomes between children from the management department or from the engineering department as a whole. However, if you look at it per statement, you can see that there is only one statement that differs significantly between the answers from management students and engineering students, namely the statement about I use e-learning as a complement to this learning, which means that the answers of students majoring in management are on average higher than the average. the answer of students majoring in engineering, meaning that more management students use e-learning to complement their learning.